2011
DOI: 10.1007/s00380-011-0146-0
|View full text |Cite
|
Sign up to set email alerts
|

Off-pump surgery for the poor ventricle?

Abstract: Severely decreased ejection-fraction is an established risk-factor for worse outcome after cardiac surgery. We compare outcomes of off-pump coronary artery bypass grafting (OPCAB) and on-pump CABG (ONCABG) in patients with severely compromised EF. From 2004 to 2009, 478 patients with a decreased EF B35% underwent myocardial-revascularization. Patients received either OPCAB (n = 256) or ONCABG (n = 222). Propensity score (PS), including 50 preoperative risk-factors, was used to balance characteristics between g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
3
8
0
Order By: Relevance
“…Some studies suggest that OPCAB reduces cardiac complications and even benefit high-risk patients in regard to stroke prevention, less postoperative morbidity and mortality (5,(10)(11)(12). Cardioplegic arrest and CPB have been the mainstays of CABG surgery for almost 30 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies suggest that OPCAB reduces cardiac complications and even benefit high-risk patients in regard to stroke prevention, less postoperative morbidity and mortality (5,(10)(11)(12). Cardioplegic arrest and CPB have been the mainstays of CABG surgery for almost 30 years.…”
Section: Discussionmentioning
confidence: 99%
“…To large extent, the surgery reduces the recurrence of myocardial ischemia and the demand of revascularization (2). For elderly patients and patients with diabetes mellitus, renal insufficiency, poor left ventricular ejection fraction (LVEF) (≤35%), peripheral vascular disease, left main CAD and chronic obstructive pulmonary disease (COPD), off-pump coronary artery bypass (OPCAB) grafting is associated with lower operative combination and mortality than on-pump coronary artery bypass (ONCAB) (3)(4)(5)(6). For patients with giant left ventricle, few reports are available (7).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that OPCAB is a safe and efficient choice for high‐risk patients with multiple organ failure 18 . Considering the advantages of the OPCAB procedure, an increasing number of surgeons are trying to extend the surgery to high‐risk patients, including women and patients with low LVEF 19,20 …”
Section: Discussionmentioning
confidence: 99%
“…18 Considering the advantages of the OPCAB procedure, an increasing number of surgeons are trying to extend the surgery to high-risk patients, including women and patients with low LVEF. 19,20 However, despite the enthusiasm for OPCAB among surgeons, its widespread adoption in China has been slower than anticipated. 21 Considering the inconsistencies among different reports, the use of OPCAB in LVD patients should be limited in real practice.…”
Section: Discussionmentioning
confidence: 99%
“…A recent published study shows that OPCAB is a safe and efficient choice for high risk patients with multiple organs failure [18]. Given the improvement and advantages of OPCAB procedure, more and more surgeons try to extend the suegery to high risk patients, including female and Low LVEF patient [19,20].…”
Section: Discussionmentioning
confidence: 99%